Selenium in human nails: a preliminar ystudy using INAA - Wee, Boon Siong; Mohd Fahmi, Abdul Rahman; Mohd Suhaimi, Hamzah (放射化分析研究会, 2013)
Selenium (Se) is an essential trace element for healthy body functions in humans. Deficiency of Se may cause diseases such as cancer and cardiovascular disease. However, Se toxicity or selenosis can also occur in humans as a result of high doses of dietary intake or industrial exposure. This study aims to use human nails for biomonitoring of Se in a healthy Malaysian adult. The results are used to assess long-term Se status and comparisons are made with literature values. Instrumental neutron activation analyses ( ...